2016
DOI: 10.18632/oncotarget.12804
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the correlation between selenium and incidence of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common cancer type. There is a correlation between selenium (Se) deficiency and the incidence of HCC. To clarify the effects of Se level on the risk of HCC patients, a meta-analysis was performed. A total of 9 articles published between 1994 and 2016 worldwide were selected through searching PubMed, EMBASE, web of science, Cochrane Library, Springer Link, Chinese National Knowledge Infrastructure (CNKI), and Chinese Biology Medicine (CBM), and the information were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Various rodent models of Wilson's disease, a hereditary disorder resulting in pathologic hepatic copper accumulation in humans, frequently develop HCC or cholangiocellular carcinoma, but a link between copper induced liver disease and HCC in actual Wilson's disease patients is controverisal . There are inverse relationships between hepatic selenium and zinc concentrations and HCC . Excess copper and iron induce oxidative stress in tissues, whereas both zinc and selenium have important antioxidant properties .…”
Section: Introductionmentioning
confidence: 99%
“…Various rodent models of Wilson's disease, a hereditary disorder resulting in pathologic hepatic copper accumulation in humans, frequently develop HCC or cholangiocellular carcinoma, but a link between copper induced liver disease and HCC in actual Wilson's disease patients is controverisal . There are inverse relationships between hepatic selenium and zinc concentrations and HCC . Excess copper and iron induce oxidative stress in tissues, whereas both zinc and selenium have important antioxidant properties .…”
Section: Introductionmentioning
confidence: 99%
“…7,[37][38][39] Se plays a major role in cellular redox status and an important regulatory role for normal bone metabolism. 20,40 It has been reported that selenium decient young male rats had low BMD, osteopenia and growth retardation. 41 Studies in mice indicated that Se deciency increased bone resorption and had detrimental effects on bone microarchitecture resulting from decreasing antioxidative potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, no relationship was observed between plasma selenium concentration and incidence of HCC in a study with Japanese hepatoma patients [72]. In 2016, a systemic review meta-analysis involving 9 trials and a total of 1433 subjects supported an inverse correlation between Se level and the risk of HCC, and lowered Se level had a relationship with HCC with a remarkable heterogeneity (I2 = 74.3%, P < 0.001) [4]. However, epidemiological investigations and biological studies should be further conducted to demonstrate and verify whether selenium supplements are beneficial for the prevention and treatment of HCC and to elucidate its exact mechanism of action.…”
Section: Epidemiological Investigations and Clinical Trialsmentioning
confidence: 99%
“…While early observational studies have shown that the trace element selenium in the environment is closely related to the occurrence and development of tumors [3]. The incidence of cancer in patients with selenium deficiency is significantly increased, and the amount of selenium in the body is negatively correlated with cancer [4]. Furthermore, while some studies suggested selenium supplementation reduces the risk of cancer, some methodologically sound trials suggested selenium supplementation does not reduce the risk of cancer and may even increase it for some types, including advanced prostate cancer and skin cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation